Banned Books : Informal Notes on some Books Banned for Various Reasons at Various Times and in Various Places - Haight, Anne Lyon (London George Allen & Unwin Ltd, 1955)
Include Appendix and Index
Keywords: Rogers, Bruce, 1870-1957 [Former owner] -- Haight, Anne Lyon